Managing Sustainable Luxury and Digitalization: Technology Trends and Ethical Challenges in the Swiss Luxury Watch Business - Mario D. Schultz; Peter Seele (Routledge, 2024)
This book offers new transdisciplinary perspectives on luxury, exploring the topical phenomenon of digitally retouched (censored) and blockchain-secured (sensored) luxury watches and outlining implications that emerge for the field of luxury studies and managerial practice. Based on a cross-disciplinary approach, the book integrates theoretical and empirical perspectives to advance the readers' understanding of luxury. With a particular focus on the Swiss luxury watch context, the book thereby draws on qualitative, quantitative, and archival data to shed new light on recent luxury trends, integrating literature on aesthetics of labour, conspicuous consumption, Gestalt theory, ethical theory, functional theories of attitudes, and surveillance studies. Eight chapters take the readers through a range of topical challenges arising with the display and changing moral perceptions of luxury and shifts that the luxury watch sector is facing in light of the digital transformation impacting luxury goods and the luxury management environment. This unique book will be of value for academics, scholars, and upper-level students across management studies with a particular interest in the luxury and fashion industries, luxury management, brand management, business ethics, and digital transformation. With a foreword by Thomaï Serdari, Leonard N. Stern School of Business, New York University.
Keywords: 650; censored luxury; sensored luxury; luxury watch industry; Rolex; counterfeit